Mathematics of parallel stratagems - Lim, Li Feng. (2012)
In recent years, financial markets around the world have been trading heavily not only on stocks but on financial derivatives such as options. Options trading shot to popularity when the Black and Scholes option pricing model was created to effectively quantify a fair option price. Black and Scholes came up with a model with help of geometric Brownian motion of particles, stochastic calculus and risk neutral measures. The resulting equation, termed as the Midas formula for the decade turned out to resemble that of a heat diffusion equation in thermodynamics.